PERSONAL PRONOUNS OF DHAO IN EASTERN INDONESIA - Jermy I. Balukh (Linguistik Indonesia, 2015)
This paper describes the properties of personal pronouns in Dhao, a language spoken by about 3000 people mainly on the island of Ndao in East Nusa Tenggara (NTT). Dhao is genetically classified into Sumba-Hawu subgroup of Central Malayo-Polynesian (CMP) branch of Austronesian languages. The focus of this paper is to describe the pronominal system of Dhao, highlighting different types of pronouns and their syntactic distribution. Dhao has three sets of morphologically independent personal pronouns and one set of bound form (affixes). The three sets can occur as independent clausal arguments, except for the clitics nga ‘1PL-ex’ and two variants of 3SG clitics which differ in syntactic distribution. As for the bound forms, the affixes are cross-referenced with NPs or full pronouns in subject positions. Personal pronouns also co-occur with other constituents as identifying expressions.